Side effects of topical atropine 0.05% compared to 0.01% for myopia control in German school children: a pilot study - Joachimsen, Lutz; Farassat, Navid; Bleul, Tim; Böhringer, Daniel; Lagrèze, Wolf A.; Reich, Michael (International ophthalmology, 2021)
Purpose Based on findings of the Asian low-concentration atropine for myopia progression study, a concentration of 0.05% has been proposed as a good compromise between safety and efficacy for myopia control. However, no data on side effects have been published so far in Caucasian children receiving this dose. Methods Prior to commencement of bilateral atropine treatment with 0.05% atropine, 19 myopic children aged 5 to 15 years were treated in only one eye at bedtime leaving the other eye as a control. Pupil size, accommodation amplitude and near visual acuity were measured at 10:00 a.m. the next day and compared to the untreated contralateral control eye. The results were then compared to a cohort of 18 children whose treatment with 0.01% atropine commenced in a similar fashion. Results Twelve children (63%) reported visual impairment or reading difficulties. Anisocoria was 2.9 ± 1.1 mm. In comparison, 0.01% atropine led to a significantly less anisocoria of 0.8 ± 0.7 mm ( p < 0.0001). Accommodation was decreased by − 4.2 ± 3.8 D in 0.05% atropine treated eyes, whereas 0.01% atropine induced hypoaccommodation of − 0.05 ± 2.5 D ( p < 0.01). Near visual acuity was not significantly reduced in eyes treated with 0.05% atropine compared to 0.01% atropine ( p = 0.26). Conclusion Compared to 0.01%, our data indicate stronger more relevant side effects of 0.05% topical atropine in young Caucasian children with progressive myopia as recently reported in Asian children, potentially compromising acceptance and compliance.